Estudo da atividade do salicilato de Borneol, um derivado salicílico, em modelos experimentais de inflamação aguda. - Vasconcelos, Renata Marcia Costa (2012)
Bornyl Salicylate (BS) is a salicylic derivative, obtained by sterification of salicylic acid and monoterpene (-)-borneol, and its topical use in inflammatory diseases has been described in the beginning of 20th century. It is also known that salicylic derivatives have anti-inflammatory activity and borneol have neuroprotective, genoprotective and analgesic activity. The goal of this study was to evaluate activity of BS in experimental models of acute inflammation. The toxicity of BS was analyzed by measuring water and food intake, weight, mortality and weight of major organs. To assess its anti-inflammatory effect, mice pre-treated with BS were subjected to carrageenan, prostaglandin E2, bradikynin or histamine-induced paw edema, zymosan-induced peritonitis and increased vascular permeability induced by acetic acid. NO production was analyzed in peritoneal macrophage cell culture. There were no signs of acute toxicity with the administration of 1000 mg/kg BS in male and female mice. Furthermore, pretreatment with BS was significantly (p<0.05) effective in reducing paw edema induced by carrageenin in early and late times; this effect is related to eicosanoid mediators and bradikynin, and independent of histamine. Neutrophils migration and the release of pro-inflammatory cytokines (TNF-, IL-1 and IL-6) induced by zimosan, and the fluid leakage induced by acetic acid were also reduced in animals treated with BS. In vitro, BS reduced NO release in LPS-stimulated macrophage. These data suggest that BS has anti-inflammatory effects related to different mechanisms of inflammation, and further studies are needed to explore its potential.